THE RENAISSANCE AND GEOFFREY CHAUCER’S LIFE AND LITERARY CAREER THE POETRY OF RENAISSANCE - Qadirova Dilnura , (TADQIQOTLAR.UZ, 2023)
Abstraction: We know the Renaissance means re-birth. From about 1500 to 1600 the world was reborn in many ways. The Renaissance began in Italy, especially in art and architecture, in the fifteenth century. As England became the most powerful nation in Europe in the late sixteenth century, new worlds were discovered and new ways of seeing and thinking developed. Columbus discovered America in 1492, Copernicus and Galileo made important discoveries about the stars and planets, Ferdinand Magellan sailed all round the world. The Renaissance was worldwide.The Renaissance period cultivated a new change in art, knowledge, and culture. It changed the way the citizens thought, with first the rediscovery of classical philosophy, literature, and art, as well as the new discoveries in travel, invention, and style.